2020
DOI: 10.5937/straman2001021p
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking in human resource management in focus of Central and Eastern Europe in the light of CRANET research

Abstract: In the Central and Eastern European (CEE) countries within the framework of the previous economic system, there were only traces of the features of modern human resource management (HRM). Since the political and economic changes, major transformation in the HRM practice has occurred, resulting in a development of the organizational position, role and practices of HR activity in the Central and Eastern European countries. The aim of our benchmark study is to compare the HRM practice of the CEE region with the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…At the same time, at the level of the entire sample, respondents show the second-highest degree of agreement regarding the average grade for this indicator (SD = 0.65). This result is expected for the Western Balkans region, where many previous studies [16][17][18] have confirmed that employees have high confidence in legal and statutory norms and believe that they ensure socially responsible corporate behaviour. Next in importance is the packaging waste management indicator (M = 4.13; SD = 0.72).…”
Section: Resultssupporting
confidence: 55%
“…At the same time, at the level of the entire sample, respondents show the second-highest degree of agreement regarding the average grade for this indicator (SD = 0.65). This result is expected for the Western Balkans region, where many previous studies [16][17][18] have confirmed that employees have high confidence in legal and statutory norms and believe that they ensure socially responsible corporate behaviour. Next in importance is the packaging waste management indicator (M = 4.13; SD = 0.72).…”
Section: Resultssupporting
confidence: 55%
“…Prior to the end of 1980s, HRM activities in most of Eastern Europe were under tight state regulation, in other words, under the control of the Communist Party (Koubek & Brewster, 1995;Poór et al, 2017). Key positions and selection of specialists had been closely controlled by the Communist Party and government policies (Kazlauskaitė & Bučiūnienė, 2010;Poór et al, 2020); the mix of collective and individual leadership elements was presented as an optimal form of management. In the previous regime, the Personnel Department was primarily directed by the Managing Director, and the scope of the Personnel Department's duties was selection and career management (M. .…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The studies of Poór et al (2020) based on longitudinal and international comparisons show that although the Central and Eastern European region and the human resource management practices of single CEE countries have brought about a variety of changes in the first two decades of the 21st century, their deviations from different regions of the world, as well as their solutions, prevailed as well.…”
Section: The Labour Market Of Central and Eastern Europementioning
confidence: 99%